Economic issues of crop based ethanol production for energetic uses - Kozár, László (Acta Agraria Debreceniensis, 2001)
The United States Congress passed the “Clean Air Act” in 1990, which targeted the creation and use of so-called “green fuel”. This Act came into full force on January 7, 1995. Its essence is that an oxygen rich component is added to fuel by which it burns more cleanly and harmful emissions of vehicles are reduced by 25%. This oxygen rich component is basically ethanol and its ether ETBE, made of domestically produced grains. America’s traditional grain exporter status could be converted into a stabile income resource during production, many more valuable by-products – should this program succeed – are also produced, giving the opportunity for further utilisation either in the foods or form feeds industries, or as export products. Ethanol or ETBE production is also important to replace fuel imports from any specific country, the additive which is necessary for producing the fuel is the imported product MTBE. This programme therefore simultaneously assisted in environmental protection, agricultural and foreign trading issues as well as some market regulation issues. At the same time, based on grain production, it has an effect on the social strata by creating new jobs, especially in those areas which can be considered in recession due to the lack of any large-scale industrial cities. In the future, the European Union should carry out this project and it will affect Hungary, as well.